2006
DOI: 10.1016/j.jasms.2005.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of specific noncovalent complexes between guanidinium derivatives and single-stranded DNA by MALDI

Abstract: Noncovalently bound complexes between highly basic sites of 12 guanidinium compounds and single-stranded DNA were studied using matrix-assisted laser desorption/ionization (MALDI) mass spectrometry. 6-Aza-2-thiothymine (ATT) was used as the matrix in the presence of ammonium citrate, and spectra were recorded in the positive ion mode. Detailed control experiments confirmed unambiguously the high selectivity and specificity of the guanidinium moiety for phosphate groups of DNA. The results verify the binding st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
17
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…This suggests that the geometry of the complex can play a role and/or that forces other than ionic ones are involved. Vasseur et al [19]âusedâMALDI-TOFâtoâobserveâcomplexesâbetween single-stranded oligonucleotide and guanidine derivatives (guanidine being the basic site of the arginine residues). They showed that the presence of an aromatic ring permitted a better interaction, pointing out the importance of complementary hydrophobic forces and -stacking.…”
mentioning
confidence: 99%
“…This suggests that the geometry of the complex can play a role and/or that forces other than ionic ones are involved. Vasseur et al [19]âusedâMALDI-TOFâtoâobserveâcomplexesâbetween single-stranded oligonucleotide and guanidine derivatives (guanidine being the basic site of the arginine residues). They showed that the presence of an aromatic ring permitted a better interaction, pointing out the importance of complementary hydrophobic forces and -stacking.…”
mentioning
confidence: 99%
“…Noncovalent complexes involving polybasic peptides and DNA have been detected by MALDI-TOF [13][14][15][16][17][18]. The first observation of such complexes was reported by Juhasz and Biemann [13]: highly acidic compounds (such as DNA) were detected as noncovalent complexes with a peptide or a small protein rich in arginine, lysine and/or histidine.…”
mentioning
confidence: 99%
“…Subsequently, Woods et al [15] used this matrix to observe complexes between various basic peptides and single/ double stranded DNA. ATT (at times in the presence of ammonium citrate) has been successfully used also to observe other complexes involving DNA and derivatives of guanidinium (which is the basic site of the arginine residues) [16] or peptides [17,18], or between two peptides bound by ionic bonds [8, 20 -22]. In all these reports focusing on acid/base interactions, guanidinium seemed to play an important role as the basic site.…”
mentioning
confidence: 99%
“…Recently, 21mers RNA was first successfully sequenced by acid hydrolysis with MALDI MS [8]. (3) Non-covalent binding [9][10][11] interactions between RNA, single/double stranded DNA, quadruplex DNA or hairpin DNA and peptides, polyamine, guanidinium derivatives, acridine, or stilbazolium ligands have been successfully analyzed. However, even with the advantages of the rapidity, simplicity, and using primarily single charged ions, MALDI MS is less frequently used to study non-covalent complexes than ESI MS. (4) Quantitative analysis.…”
Section: Introductionmentioning
confidence: 99%